INTERNALISASI PENDIDIKAN KARAKTER DALAM GERAKAN LITERASI BERBASIS KEARIFAN LOKAL - Rofiatun Nisa’ (CENDEKIA, 2019)
The purpose of research is to describe the character education in the local wisdom-based literacy movement using text that is close to the environment of students and the implementation of character education in the local wisdom-based literacy movement. The research method uses a descriptive qualitative approach. Data collection techniques using observation, interviews, documentation. Data were analyzed by reducing data, presenting data and drawing conclusions. The results showed that character education in the literacy movement based on local wisdom is curiosity, communicative, fond of reading, discipline, creative and responsibility. The internalization of character educators in the literacy movement based on local wisdom is to use a variety of strategies such as utilizing texts from environmental observations that exist near students, regional saga texts and folklore. Evaluation is carried out by writing notes in the student's reading record book and data values ​​to find out the competencies that have been mastered by students.